MENGKAJI PENTINGNYA ETIKA DALAM PRAKTIK BISNIS PADA PASAR RITEL MODERN - PRICILLIA, MELLISA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This paper aims to examine the importance of ethics in business practices in the modern retail market. Business ethics are the standards of value that guide or reference managers and all employees in decision-making and operating business ethics. Changes in world trade demands immediate repaired business ethics that improved world economic order. In the modern retail market business is not uncommon to apply the concept ends justify any means. Even smelling criminal action was taken for the business world but it does not seem to show the opposite trend, rising increasingly. One step in the implementation of ethical business practices are ethical business practices in the modern retail market. Through ethical business practices, so much so that the learning gained a sound and ethical business can become a reality